MiR-330-5p targets SPRY2 to promote hepatocellular carcinoma progression via MAPK/ERK signaling. (November 2018) - Xiao, Shuai; Yang, Mengyuan; Yang, Hao; Chang, Ruimin; Fang, Feng; Yang, Lianyue
Abstract MicroRNAs (miRNAs) have been identified as critical modulators of cell proliferation and growth, which are the major causes of cancer progression including hepatocellular carcinoma (HCC). Our previous miRNA microarray data have shown that miR-330-5p was always upregulated in HCC. However, the accurate role of miR-330-5p in HCC is still uncertain. Here, we report that miR-330-5p expression is upregulated in HCC tissues and cell lines, and is associated with tumor size, tumor nodule number, capsule formation and Tumor Node Metastasis (TNM) stage in HCC patients. Overexpression of miR-330-5p promotes proliferation and growth of HCC cells in vitro and in vivo, while miR-330-5p knockdown has the inverse effect. Moreover, using miRNA databases and dual luciferase report assay, we find miR-330-5p directly binds to the 3′-untranslated region (3′-UTR) of Sprouty2 (SPRY2). Then we find the novel biofunctional role of SPRY2 inactivation in promoting HCC progression. Finally, we confirm that miR-330-5p suppresses SPRY2 to promote proliferation via mitogen-activated protein kinases (MAPK)/extracellular regulated kinase (ERK) signaling in HCC. Taken together, our findings demonstrate the critical role of miR-330-5p in promoting HCC progression via targeting SPRY2 to activate MAPK/ERK signaling, which may provide a novel and promising prognostic marker and therapeutic target for HCC.